An evaluation of progression free survival and overall survival of ovarian cancer patients with clear cell carcinoma versus serous carcinoma treated with platinum therapy: An NRG Oncology/Gynecologic Oncology Group experience - Oliver, Kate E (Gynecol Oncol, 2017)
PURPOSE: We examined disparities in prognosis between patients with ovarian clear cell carcinoma (OCCC) and serous epithelial ovarian cancer (SOC). METHODS: We reviewed data from FIGO stage I–IV epithelial ovarian cancer patients who participated in 12 prospective randomized GOG protocols. Proportional hazards models were used to compare progression-free survival (PFS) and overall survival (OS) by cell type (clear cell versus serous). RESULTS: There were 10,803 patients enrolled, 9,531 were eligible, evaluable and treated with platinum, of whom 544 (6%) had OCCC, 7,054 (74%) had SOC, and 1,933 (20%) had other histologies and are not included further. In early stage (I–II) patients, PFS was significantly better in OCCC than in SOC patients. For late stage (III, IV) patients, OCCC had worse PFS and OS compared to SOC, OS HR= 1.66 (1.43, 1.91; p<0.001. After adjusting for age and stratifying by protocol and treatment arm, stage, performance status, and race, OCCC had a significantly decreased OS, HR= 1.53 (1.33, 1.76; p<0.001). In early stage cases, there was a significantly decreased treatment effect on PFS for consolidative therapy with weekly Paclitaxel versus observation in OCCC compared to SOC (p=0.048). CONCLUSIONS: This is one of the largest analyses to date of OCCC treated on multiple cooperative group trials. OCCC histology is more common than SOC in early stage disease. When adjusted for prognostic factors, in early stage patients, PFS was better for OCCC than for SOC; however, in late-stage patients, OCCC was significantly associated with decreased OS. Finally, treatment effect was influenced by histology.